2021
DOI: 10.46497/archrheumatol.2022.8838
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein-associated phospholipase A2 and carotid intima-media thickness in primary Sjögren syndrome

Abstract: Objectives: This study aims to evaluate serum lipoprotein-associated phospholipase A2 (Lp-PLA2) level and carotid intima-media thickness in primary Sjögren syndrome (pSS) as an indicator of atherosclerosis. Patients and methods: Between July 2019 and July 2020, a total of 33 female pSS patients (mean age: 44.5±11.2 years; range, 23 to 60 years) and 37 female age- and sex-matched healthy individuals (mean age: 40.9±7.2 years; range, 25 to 54 years) were included. Carotid intima-media thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The mechanisms for cardiovascular involvement remain unknown. Various studies have identified endothelial dysfunction, carotid intima-media thickness changes with resulting loss in vessel wall compliance in pSS patients [ 260 , 268 ]. Persistent endothelial dysfunction-related subclinical atherosclerosis may be found in pSS patients, who have increased values of circulating endothelial microparticles, endothelial progenitor cells [ 257 ], and angiotensin [ 269 ].…”
Section: Extraglandular Manifestationsmentioning
confidence: 99%
“…The mechanisms for cardiovascular involvement remain unknown. Various studies have identified endothelial dysfunction, carotid intima-media thickness changes with resulting loss in vessel wall compliance in pSS patients [ 260 , 268 ]. Persistent endothelial dysfunction-related subclinical atherosclerosis may be found in pSS patients, who have increased values of circulating endothelial microparticles, endothelial progenitor cells [ 257 ], and angiotensin [ 269 ].…”
Section: Extraglandular Manifestationsmentioning
confidence: 99%